Pengaruh Penggunaan Fintech dan Literasi Keuangan terhadap Inklusi Keuangan - Faidatul Ainiyah; Indah Yuliana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
AbstractThis study aims to determine and analyze the effect of using fintech and financial literacy on financial inclusion. This research is motivated by the importance of increasing financial inclusion by using fintech among students. The method used in this research is quantitative through descriptive analysis approach. Collecting data using questionnaires using research samples Postgraduate students at the State Islamic University of Malang totaling 100 students. This study uses PLS Smart 3.0 as a tool to analyze data. The results of this study indicate that financial literacy has a significant effect on financial technology, the use of financial technology has a significant effect on financial inclusion, financial literacy has a significant effect on financial inclusion.